The Effect of External and Internal Factors on Financial Management of Salt Business Actors - Nikmah, Wardatun; Nugroho, Prasetyo; Purnomo, Arie Setyo Dwi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The salt industry is one of the important sectors that contribute to the regional economy in Indonesia, where business actors in the salt industry face intense competition, so effective financial planning is crucial to survive and thrive. Good financial management can increase competitiveness and minimize financial risk. However, many business actors do not yet understand the importance of responsible financial management. This study aims to analyze the influence of external factors, such as climate change, government policies and competition in the industry, as well as internal factors, such as financial planning and sources of financing or funding, on the financial management of salt business actors in Pamekasan. Despite having great potential, business actors often face challenges from external factors, such as unpredictable weather and competition in the salt industry. The results of the study are expected to provide insight for business actors in optimizing financial management to improve business performance and contribution to national income.